2004
DOI: 10.2144/04371rr01
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference by osmotic lysis of pinosomes: liposome-independent transfection of siRNAs into mammalian cells

Abstract: The osmotic lysis of pinosomes procedure has been adapted to deliver small interfering RNAs (siRNAs) into cells in culture. Under hypertonic conditions, siRNAs were internalized into pinosomes. A subsequent osmotic shock in hypotonic buffer disrupted the pinosomes and caused the release of siRNAs into the cell cytoplasm. Both steps could be demonstrated directly using fluorescein-labeled siRNAs and confocal laser-scanning microscopy. Uptake by the pinocytosis/osmotic lysis procedure is concentration- and time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Drugs 784 Proteins, 108,780,781,785,787 Cas9 RNPs Laser-Induced Cavitation Dyes 487,879,914,918,919,922,926,928,929,1580,1581 Proteins, 340,919 Antibodies 1325 siRNA, 1042,1043 Antisense oligonucleotides, 1038 Antisense morpholinos 804 qDots, 1594 Proteinconjugated qDots 306,1040,1041 Virus particles 1039…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drugs 784 Proteins, 108,780,781,785,787 Cas9 RNPs Laser-Induced Cavitation Dyes 487,879,914,918,919,922,926,928,929,1580,1581 Proteins, 340,919 Antibodies 1325 siRNA, 1042,1043 Antisense oligonucleotides, 1038 Antisense morpholinos 804 qDots, 1594 Proteinconjugated qDots 306,1040,1041 Virus particles 1039…”
Section: Discussionmentioning
confidence: 99%
“…By using up to 1.6 μM siRNA in solution, gene silencing of >50% was reproducibly achieved in common cell lines such as HEK and HeLa. 1042 In a subsequent study by a different group, improved RNAi transfection was demonstrated in hard-to-transfect immune cell lines. 1043 Their modified procedure was more extreme, involving hypertonic sucrose solutions of up to 2 M and siRNA concentrations of 10 μM.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C, upper panel). In the acidic environment of the endosome (pH 5.5-6), siRNA may detach from the lipid, and if the cationic lipid or helper lipid facilitates siRNA translocation from the endosome to the cytosol, dextran-FITC can also go through 6-nm radius transmembrane pores generated by an unknown mechanism by LNPs, possibly through osmetic lysis of pinosomes (Gruber et al 2004) or the proton sponge effect (Patil et al 2009). Therefore, diffused green signals can be detected and measured in the entire cells (Fig.…”
Section: Analyses Of Sirna Endosomal Escape and Riscloaded Sirnamentioning
confidence: 99%
“…In the pressure change‐mediated system, a hypo‐osmotic shock is induced by rapid changes in osmotic and hydrostatic pressure across the cell membrane, resulting in osmolality‐dependent permeabilization. [ 124,125 ] Hence, cells experience significant stress since their membranes face the differences in osmotic potential between the intra‐ and extracellular environment (gradients of osmotic pressure), leading to the membrane perturbation, and consequently, delivery of cargoes. [ 126 ] The geometry of these gradients may vary between the intracellular contents of target cells and the extracellular environment, facilitating the entrance of osmolytes or impermeable electrolytes through the membrane or aquaporin channels.…”
Section: Macroengineered Intracellular Deliverymentioning
confidence: 99%